Footbal quiz book - Drew, Paul; Jennings, Colin (London : Arcturus Pub., 2009)
With questions on everything the dedicated football fan could possibly want to know about the beautiful game, ranging in difficulty from the challenging to the fiendishly impossible, the football quiz book will appeal to old and young alike. With sections on all aspects of the game, from the 1960s right up to the present day, and from English non-League clubs to the winners of Euro 2008, the football quiz book is the perfect companion for every football fan with a thirst for sporting trivia.
Keywords: Football-quiz book